In Silico Design of Chimeric Peptides for Infection Resistant Implant Coatings - Yücesoy, Deniz Tanıl; Kan, İlker; Özçivici, Engin (01. Izmir Institute of Technology, 2023)
Tooth loss has been a widespread dental problem affecting patients of various ages. Replacement of lost teeth with implants is a common practice for managing tooth loss due to their mechanical properties and natural-looking aesthetics. One of the persistent problems associated with dental implants is the risk of infection (periimplantitis) which can occur when bacteria colonize the implant surface leading to inflammation and tissue damage with an eventual implant failure. Infection-resistant antimicrobial coatings have been one of the promising solutions to combat implant infections. The purpose of this study was to design functional chimeric peptides using antimicrobial peptides and hydroxyapatite binding peptides in order to provide an antimicrobial effect to hydroxyapatite-coated titanium dental implants. For this purpose, since titanium implants coated with hydroxyapatite show long-term biocompatibility, chimeric peptides that can provide antimicrobial resistance have been designed by considering antimicrobial peptides in addition to these coatings. Computational analysis, solubility analysis, secondary structure analysis, and conformational change analysis were performed to examine the ability of these formed chimeric peptides to retain their antimicrobial properties. Promising candidates obtained from secondary structure analysis and solubility analysis were examined to preserve their structure and stability by performing conformational change analysis, and the most suitable candidates were decided. Although the results give candidates computationally according to the analysis, these candidates should be confirmed experimentally. When the results from the computational analysis are validated by the experimental analysis, it will set the standard for antimicrobial chimeric peptide design.

Diş kaybı, çeşitli yaşlardaki hastaları etkileyen yaygın bir problem olmuştur. Kaybedilen dişlerin implantlarla değiştirilmesi, mekanik özellikleri ve doğal görünümlü estetikleri nedeniyle diş kayıplarını telafi etmek için yaygın bir uygulamadır. Dental implantlarla ilişkili kalıcı sorunlardan biri, bakterilerin implant yüzeyini kolonize ederek enflamasyona, doku hasarına ve nihai bir implant başarısızlığına yol açtığındaki ortaya çıkabilen enfeksiyon (peri-implantitis) riskidir. Enfeksiyona dirençli antimikrobiyal kaplamalar, implant enfeksiyonlarıyla mücadelede umut verici çözümlerden biri olmuştur. Bu çalışmanın amacı, hidroksiapatit kaplı titanyum dental implantlara antimikrobiyal etki sağlamak için antimikrobiyal peptidler ve hidroksiapatit bağlayıcı peptid kullanarak fonksiyonel kimerik peptidler tasarlamaktır. Bu amaç ile, hidroksiapatit ile kaplanmış Titanyum implantlar uzun vadeli biyouyumluluk gösterdiği için bu kaplamalara ek olarak antimikrobiyal peptitler ele alınarak antimikrobiyal direnç sağlayabilecek kimerik peptitler dizayn edilmiştir. Oluşturulmuş bu kimerik peptitlerin antimikrobiyal özelliklerini koruyabildiklerini incelemek için hesaplamalı olarak ikincil yapı analizi, çözünürlük analizi ve konformasyonel değişim analizi yapılmıştır. İkincil yapı analizi ve çözünürlük analizinden elde edilen umut vadeden adayların konformasyonel değişim analizi yapılarak yapısını ve stabilitesini korumaları incelenmiş olup en uygun adaylara karar verilmiştir. Sonuçlar, yapılan analizlere göre hesaplamalı olarak adayları veriyor olsa da bu adaylar deneysel olarak konfirme edilmelidir. Hesaplamalı analiz ile elde edilecek sonuçlar deneysel analiz ile valide edildiğinde antimikrobiyal kimerik peptit dizaynı için bir standart oluşturmuş olacaktır.
Enfeksiyona Dirençli İmplant Kaplamaları için İn Silico Kimerik Peptit Tasarımı
Thesis (Master)--İzmir Institute of Technology, Bioengineering, Izmir, 2023
Includes bibliographical references (leaves. 56-82)
Text in English; Abstract: Turkish and English
Keywords: Dental implants; Periimplantitis; Surface coating; Chimeric peptides